PROPOSED IMPROVEMENT OF SERVICE QUALITY PERFORMANCE USING MODIFIED IMPORTANCE PERFORMANCE ANALYSIS AT DâGYM FITNESS CENTER - Theo Buditama, Adithia
D'Gym Fitness Center is one of the fitness centers in the city of Cirebon. From September 2021 to September 2022 there was a decrease in active members due to poor service quality, so an appropriate strategy is needed in terms of improving service quality. Service quality measurement in terms of performance is carried out to help analyze service quality at D'Gym Fitness Center. The Modified Importance Performance Analysis (MIPA) method is used to compare the performance of D'Gym Fitness Center with DoctorFit Fitness Center as a competitor company. Using the MIPA method, comparative data is obtained between the company's performance and the performance of its main competitors. This makes it easier to determine service quality improvement proposals that are in line with consumer expectations. There are 23 attributes used to measure service quality performance. From the results of data processing performed company performance values and relative performance index values are obtained. These attributes are mapped into four quadrants based on these values. Of the four quadrants, there are 14 attributes that are priority improvements. Attributes that are prioritized for improvement include cleanliness, modern facilities, and employees who are responsive to complaints. Examples of improving these attributes are repairing air conditioners, upgrading gym equipment, and responsiveness in responding to complaints submitted by its members.